Carbamate herbicides—new tools for cytological studies - W Storey; L Jordan; J Mann (California Agriculture, 1968)
Cytology (the branch of biology dealing with studies of cell structure and function under the microscope) is important to both plant and animal scientists, because cytological studies disclose useful information on cell organization and behavior under both normal and artificially induced conditions. Plant physiologists in the Department of Horticultural Science, Riverside, are actively engaged in research on herbicides, with special emphasis on selective elimination of weeds from plantings of crop plants. In some experiments, the effects of herbicides become immediately apparent in either the weeds or the crop plants, or in both. In other experiments, damage to both weeds and crop plants remains concealed for a long time before it becomes evident. Such variable and often unpredictable behavior explains the interest of weed control physiologists in the mode of action of selective herbicides upon the species under study. One of the more promising approaches to mode-of-action studies is the cytological examination of herbicidal effects upon individual cells, especially dividing cells in root tissues.